Service Failure and Recovery: The Best Defense Is a Good Attack - Dewi Wuisan; Hendra Achmadi; Oscar Jayanagara; Sylvia Samuel; Gracia Shinta S. Ugut (Universitas Pelita Harapan, 2025)
Service failure is an inevitable aspect of any service-oriented business. When failures occur, the organization’s response is critical in shaping customer perceptions, satisfaction, and loyalty. This paper explores the notion that